2022
DOI: 10.1115/1.4055720
|View full text |Cite
|
Sign up to set email alerts
|

A Proof-of-Concept Study on an Internal-Resonance-Based Piezoelectric Energy Harvester With Coupled Three-Dimensional Bending-Torsion Motions

Abstract: By exchanging the internal energy between coupled vibration modes, internal-resonance-based energy harvesters may provide an effective solution to broadening and enhancing bandwidth and power performance in dealing with natural vibration sources. With the development of piezoelectric-based transducers, thickness and face shear coefficients in proper piezoelectric elements can also generate the power output from shear deformation on the core vibrating elements. However, in most cantilever-based energy harvester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Additionally, a wideband two‐element piezoelectric energy harvester exhibiting both bistability and parametric resonance characteristics is presented 23 . Furthermore, Fan introduced an internal resonance piezoelectric energy harvester featuring three‐dimensionally coupled bending and torsional modes 24 . More recently, Pan et al 25 proposed a new concept by integrating bi‐stability and swinging balls to harvest wind energy and experimental results indicated that the design achieved a significant improvement in electric outputs due to its ability to realize snap‐through motions over a wide range of wind speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a wideband two‐element piezoelectric energy harvester exhibiting both bistability and parametric resonance characteristics is presented 23 . Furthermore, Fan introduced an internal resonance piezoelectric energy harvester featuring three‐dimensionally coupled bending and torsional modes 24 . More recently, Pan et al 25 proposed a new concept by integrating bi‐stability and swinging balls to harvest wind energy and experimental results indicated that the design achieved a significant improvement in electric outputs due to its ability to realize snap‐through motions over a wide range of wind speed.…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, Fan introduced an internal resonance piezoelectric energy harvester featuring threedimensionally coupled bending and torsional modes. 24 More recently, Pan et al 25 proposed a new concept by integrating bi-stability and swinging balls to harvest wind energy and experimental results indicated that the design achieved a significant improvement in electric outputs due to its ability to realize snap-through motions over a wide range of wind speed. To enhance the efficiency of energy harvesting from vibrations characterized by low excitation levels and a broad frequency spectrum, a variety of nonlinear configurations exhibiting tristable, [26][27][28] quad-stable, 29,30 and penta-stable 31,32 characteristics have been proposed and investigated theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Aravindan and Ali (2021) analyzed the nonlinear dynamics behaviors and harvesting performance of a one-to-three internally resonant piezoelectric cantilever beam with a lumped mass under harmonic excitation and showed that the higher mode invoked through internal resonance plays a significant role in broadband power generation. Fan et al (2022b) presented an internal resonance piezoelectric energy harvester with three-dimensional coupled bending and torsional modes and shown that the fine-tuned system leverages a two-to-one internal resonance between its first torsion and second bending modes to enhance the power output. Huang et al (2023) designed a TDOF U-shaped single magnet bistable energy harvester based on the internal resonance technique and demonstrated the proposed system can produce a significant output in two frequency ranges.…”
Section: Introductionmentioning
confidence: 99%
“…The omnidirectionality of wind energy harvesting can be enhanced. Fan et al [55] enhanced the power and bandwidth by utilizing internal resonance, which also broadened the overall bandwidth.…”
Section: Introductionmentioning
confidence: 99%